Gentlemen, heroes, real men, disabled men: explorations at the intersections of disability and masculinity in contemporary China - Dauncey, Sarah (Brill, 2017)
This article advances new perspectives on disability culture in contemporary China. Using gender – specifically masculinity – as an “intersection,” it addresses key questions that both help to explain, but also further trouble, the way in which the “impaired” male body is both represented and lived in China today. Although recent research across the disciplines is revealing more and more about pre-modern and contemporary understandings of, and responses to, disability in China, little is known about the way in which gendered identities intersect and interact with disabled identities. From “gentlemen” and “heroes” to “real men” and “disabled men,” this article examines dominant historical and contemporary images of masculinity and disability, and illustrates how they have come to frame the way in which disabled men have been viewed and view themselves. And, through the close reading of the memoirs of one young man, Zhang Yuncheng, it reveals the possibilities and limitations through which gendered behaviors are formed and enacted on an individual level when set against Chinese discourses of disability, normalcy, and gender.